Advanced casebook of obsessive-compulsive and related disorders : conceptualizations and treatment - Storch, Eric A.; McKay, Dean, 1966-; Abramowitz, Jonathan S. (Academic Press, 2020)
This volume presents a synthesis of the emerging data across clinical phenomenology, assessment, psychological therapies and biologically-oriented therapies regarding obsessive compulsive disorders, including hoarding, skin picking, body dysmorphic and impulse control disorders.--